Development of Digital Comic “Putri Tujuh” for Reading Course A2 - Laura Susanty; Suci Pujiastuti (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This study aims to create a digital comic from the folk tale "Putri Tujuh". This study uses the creation method. The creation process consists of an explanation of the phases of Richey and Klein's theory. Among them are (1) planning, (2) making, (3) evaluation. The data for this study are sentences in the folk tale "Putri Tujuh". The source of the research data is a book entitled "Cerita Rakyat dari Riau" by BM Syamsuddin published by Grasindo and Gramedia publishers with ISBN numbers 9789795532569 and 9795532561. The results of this study are in the form of a digital comic "Putri Tujuh" in German. This comic consists of several pages. The evaluation results show that the digital comic has an overall score of 90 (very good).